Analisis Peran Mediasi Digitalisasi Layanan Pendaftaran dan Digitalisasi Layanan Pembayaran dalam Hubungan antara Patient Experience dan Jumlah Kunjungan Pasien - Meyland Citra Oktri Sienty Effendy; Adya Hermawati; Eka Wilda Faida; Muryati Muryati; Rahayu Puji Suci (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Digital transformation in the healthcare sector requires hospitals to optimize patient-centered care services to enhance competitiveness. Hospital operational success is often reflected in the volume of patient visits, which is influenced by the quality of the patient experience and the effectiveness of administrative digitization. This study aims to analyze the influence of patient experience on the volume of patient visits, with the digitization of registration and payment services as a mediating variable at Ciputra Hospital Surabaya. A quantitative approach using explanatory research methods was applied in this study. Data were collected from 250 respondents selected through purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that patient experience has a strong unidirectional correlation with the adoption of digitalized registration and payment services. Furthermore, this digital integration has been shown to have a significant impact on increasing the volume of patient visits. Theoretically, the digitalization of registration and payment services serves as a significant mediator bridging the relationship between patient experience and patient visit decisions. These findings confirm that improving the patient experience through administrative automation can create process efficiency, ease of accessibility, and convenience, which are crucial for customer loyalty. From a managerial perspective, this study implies that strengthening digital infrastructure is a fundamental strategy for hospital management to improve service quality, strengthen market position, and ensure the sustainability of institutional competitiveness amidst the rapid digital transformation of healthcare services.